KOMUNIKASI ORGANISASI PURNA PASKIBRAKA INDONESIA JAKARTA TIMUR (PPIJT) PADA PERILAKU PURNA PASKIBRAKA - Putri, Dianingtyas M (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The organization is defined as an arrangement of people who deliberately to achieve a certain goal. The main character in an organization is human because one of the important dimensions of an organization is one of the factors and supporters of the organization. In other words, organizations also play a role in the process of forming human self-identity. This study uses organizational communication with behavioral theory and symbolic interactionism theory. Objects analyzed by members of Paskibraka in Purna Paskibraka Indonesia, East Jakarta. This research method uses a case study with a qualitative approach. Observation data analysis techniques and in-depth interviews using purposive sampling on informants. Then, the results of this study indicate that with the direction of the flow of communication from superiors to subordinates (downward communication) to the implementation of objectives and strategies can be successful, procedures and practices are carried out, instructions given by senior coaches are carried out, the basis of work provided can be done so that performance feedback can say to be appropriate, then indoctrination occurs. However, this only happens between them and is not comprehensive on all fronts. The openness of internal communication between them does not occur, such as wanting to express opinions following the object and perceptions can not be conveyed. Members-only focus on the best flag-raising exercise, because if it is not done it will cause social pressure on individuals and groups. Through organizational culture that is formed into control, the mechanism provides guidance and shapes the attitudes and behaviors of Capaska (candidate for Paskibraka). This behavior is formed from the organizational environmental process at PPIJT so that it can have implications for the ethical behavior it has, namely personality, values, moral principles. Ethical behavior also influences how individuals behave in problem solving, thought processes, communication, observation, and action. So the findings of this study are that PPIJT only focuses on the application of its output, but does not provide an in-depth understanding of Pancasila values ​​related to social interaction with others.